PENGARUH KELAS IBU HAMIL TERHADAP PENGETAHUAN DAN SIKAP IBU TENTANG PEMERIKSAAN DAN PERAWATAN KEHAMILAN DI WILAYAH KERJA PUSKESMAS BATAM TAHUN 2016 - R.Oktaviance Simorangkir; Lilis Sumardiani (STIKes Santa Elisabeth Medan, 2016)
In the Working Area of Pancur Batu Puskesmas class, pregnant women begin to be implemented in 2016, but still found the low knowledge of pregnant women about the ideal pregnancy examination and there are pregnant women who show unimportant attitude checking pregnancy to health workers. Goals : The purpose of this research is to know the influence of maternal class on pregnant mother's knowledge and attitude about pregnancy examination and treatment. Methods : The study used a quantitative method with cross sectional design. The population of 151 pregnant women in Pancur Batu Community Health Center and 132 of them (63 pregnant women who had attended pregnant mother class and 69 pregnant women who never attended maternal class) were used as samples. Data analysis using independent t test at significance level α = 0,05. Result : The results showed the total range of knowledge scores of mothers who had followed the class of pregnant women is 7-13 with an average value of 10.08 ± 1.82, while the total range of scores of mothers who never follow the pregnant women's class is 1-9 with an average value 4,97,1,94. There is a maternal class effect on maternal knowledge of examination and treatment of pregnancy (p <3,82. There is a maternal class effect on maternal attitudes about examination and treatment of pregnancy (p3.13, while the total range of maternal scores that never follow the class of pregnant women is 27-47 with an average value of 35 , 410.001). The total score of attitudes of mothers who have attended the class of pregnant women is 41-56 with an average score of 48.24 <0.001). Conclution : It is expected that the Health Office to schedule Pancur Batu Puskesmas to carry out pregnant women's classes regularly and carried out 2 periods a year. Pancur Batu Puskesmas is expected to maintain the quality of pregnant women's classes and counseling invites all pregnant women to follow the class of pregnant women.